Photocatalytic degradation of levofloxacin using zinc oxide-hydroxyapatite nanocomposite - Go, Adrian D. (Animo Repository, 2022)
Antibiotic pollution in the environment has been contributing to the increase of antibiotic-resistant bacteria. Conventional wastewater treatments plants, especially in developing countries, do not offer complete remediation of antibiotics resulting in the improper discharge of antibiotics in natural waters. Advance oxidation process (AOP) is one of the innovative methods to completely mineralize most organic compounds by introducing reactive hydroxyl radicals. Heterogeneous photocatalysis is a type of advance oxidation process that employs the use of catalyst under light irradiation to form the hydroxyl and superoxide reactive species that destroys organic pollutants. There is still a lack of viable and efficient photocatalyst up to date. Hence, there is a need for constant exploration of alternative feasible catalysts for environmental waste remediations. In this study, hydroxyapatite (HAp) and zinc-oxide-hydroxyapatite nanocomposite (ZnO-HAp) catalysts were synthesized to degrade aqueous levofloxacin under UV irradiation. Characterization of the catalysts included the crystal structure (XRD), surface morphology (SEM), internal composition (TEM), elemental composition (EDX), and functional groups (FTIR). Optimization of levofloxacin photodegradation using pure hydroxyapatite and zinc oxide-hydroxyapatite catalyst was done using the response surface method (Box Behnken model). The optimum parameters generated from the model were 1.5 g/L catalyst dose, 4 ppm Levofloxacin, pH 10 for HAp activity, and 1.3 g/L catalyst dose, 4 ppm Levofloxacin, pH 7.7 for ZnO-HAp. The predicted photodegradation efficiency was 71.6% for HAp and 99.9% for HAp-ZnO whereas the actual efficiencies were 70.6% and 91.7%, respectively. Response surface models for both HAp and ZnO-HAp were proven to have good predictability and fitting. Degradation products using zinc oxide-hydroxyapatite catalyst at optimum conditions were identified via liquid chromatography-mass spectrometry which suggested a piperazinyl removal mechanism from the Levofloxacin ring.